Historical exposure to chemicals reduces tolerance to novel chemical stress in Daphnia (waterflea). Issue 11 (15th April 2022) - Abdullahi, Muhammad; Zhou, Jiarui; Dandhapani, Vignesh; Chaturvedi, Anurag; Orsini, Luisa
Abstract: Until the last few decades, anthropogenic chemicals used in most production processes have not been comprehensively assessed for their risk and impact on wildlife and humans. They are transported globally and usually end up in the environment as unintentional pollutants, causing long‐term adverse effects. Modern toxicology practices typically use acute toxicity tests of unrealistic concentrations of chemicals to determine their safe use, missing pathological effects arising from long‐term exposures to environmentally relevant concentrations. Here, we study the transgenerational effect of environmentally relevant concentrations of five chemicals on the priority list of international regulatory frameworks on the keystone species Daphnia magna . We expose Daphnia genotypes resurrected from the sedimentary archive of a lake with a known history of chemical pollution to the five chemicals to understand how historical exposure to chemicals influences adaptive responses to novel chemical stress. We measure within‐ and transgenerational plasticity in fitness‐linked life history traits following exposure of "experienced" and "naive" genotypes to novel chemical stress. As the revived Daphnia originate from the same genetic pool sampled at different times in the past, we are able to quantify the long‐term evolutionary impact of chemical pollution by studying genome‐wide diversity and identifying functional pathways affected by historical chemical stress. Our results suggest that historical exposure to chemical stress causes reduced genome‐wide diversity, leading to lower cross‐generational tolerance to novel chemical stress. Lower tolerance is underpinned by reduced gene diversity at detoxification, catabolism and endocrine genes in experienced genotypes. We show that these genes sit within pathways that are conserved and potential chemical targets in other species, including humans.